4x-5=11x+16

Simple and best practice solution for 4x-5=11x+16 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4x-5=11x+16 equation:


Simplifying
4x + -5 = 11x + 16

Reorder the terms:
-5 + 4x = 11x + 16

Reorder the terms:
-5 + 4x = 16 + 11x

Solving
-5 + 4x = 16 + 11x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-11x' to each side of the equation.
-5 + 4x + -11x = 16 + 11x + -11x

Combine like terms: 4x + -11x = -7x
-5 + -7x = 16 + 11x + -11x

Combine like terms: 11x + -11x = 0
-5 + -7x = 16 + 0
-5 + -7x = 16

Add '5' to each side of the equation.
-5 + 5 + -7x = 16 + 5

Combine like terms: -5 + 5 = 0
0 + -7x = 16 + 5
-7x = 16 + 5

Combine like terms: 16 + 5 = 21
-7x = 21

Divide each side by '-7'.
x = -3

Simplifying
x = -3

 

You can always share this solution

See similar equations:

| 5(a+3)=3a+31 | | 4-2(x-1)=18 | | 3z+15=2z+6 | | 2x^2+3=-13 | | x^2=-9 | | X^2-7x+10=0 | | 2x^2-7x+5=0 | | 6y-2(y-5)=46 | | 2x+15=x+8x | | -12-2h=8 | | 12x+2=12x | | 7x-1=2x+9 | | -8x+1+6x=-3x+6 | | -x-13=11-5x | | 3x+2=12-5x | | 3x-8=5x-16 | | 10x-2=-8+5x | | 8x=x+28 | | -3y-9=4y+12 | | 3t-8=4(t+2) | | 3-(y-6)= | | -5(t+6)=0 | | 3(x-1)-21=0 | | -6x-12=-24 | | 35-11=4(x-3) | | 5x-3=4x-8 | | 2x-3=x-4 | | 8x=7x+15 | | 2X+2=X+1 | | 5x-2+3x=6x+8 | | 4x+3=6x+8 | | 3(10+7)=30x-1 | | 3x-2=x-2 | | 10x-19=23-4x | | 7x=-1x+18 | | 18-5y=7y-12 | | -5x+10=25 | | 4x+12=-20 | | 2x-1=2x+1 | | X-11=-4 | | X+4=-7 | | 6x+8=5x+2 | | 9x+8=9x-3 | | 6x+8=5x+8 | | 5x=4x+7 | | 2x-3=x+4 | | 3x-5(x-5)=-8+2x+1 | | 4x=x-12 | | -x-5=-2x-9 | | 2x-x+1=5 | | 6x-20=4-2x | | 0.50d-5=2 | | 6x-10=7+3x+2x | | 16p+8=2(8p+4) | | 3x+2=5x+12 | | -7x+9=-2-10x | | 3x-16=-4 | | 3(2+6x)=18x | | 4x-8=2x-2 | | 2x-2=-14 | | 6x+2=x+2 | | -2x=-12 | | 6(x-3)=9(x+5) | | 3(x+4)=21 | | 6-2x=6x-10x+6 |

Equations solver categories